Design, synthesis and analysis of Isoreticular, 2-Periodic, Co(II)/(Mn(II) mixed- and Zn(II) single-ligand metal-organic frameworks for sorption of energy- and environmentally-relevant molecules - Muguru, Kedibone Gudani (Department of Chemistry, 2026)
The study of porous materials, particularly Metal-Organic Frameworks (MOFs), has garnered significant attention due to their tunable structures and potential for diverse applications. MOFs, constructed from metal ions or clusters and organic ligands, offer structural versatility where the choice of ligand influences pore size, geometry, flexibility, and adsorption properties. Mixed-ligand MOFs, incorporating two or more distinct ligands, enhance structural complexity and enable tuning of pore features in multiple dimensions, making them highly suitable for gas sorption applications. This study reports the design, synthesis, and characterisation of novel 2-periodic, isoreticular Co(II)/Mn(II) mixed-ligand and Zn(II) single-ligand MOFs. The mixed-ligand systems, synthesised using isophthalic acid (H2ia) and 1,3-bis(4-pyridyl)propane-N,N'-dioxide (bppdo), yielded isoreticular frameworks with formulae [Co3(ia)3(bppdo)(MeOH)]n·n(DMF) (1) and [Mn3(ia)3(bppdo)(MeOH)]n·n(DMF) (2). The single-ligand systems, constructed using 4,4′-(hexafluoroisopropylidene)bis(benzoic acid) (H2hfipbb), produced two pairs of MOFs: doubly interpenetrated frameworks [Zn(hfipbb)(MeOH)]n·n(MeOH)0.5 (3) and [Zn(hfipbb)(EtOH)]n·n(EtOH)0.5 (4) and non-interpenetrated frameworks [Zn2(hfipbb)2(DMF)2]n·n(DMF)4 (5) and [Zn4(hfipbb)4(DMA)4]n·n(DMA)8·n(H2O) (6). The ligands' unique rigidity and functionality yielded MOFs with varying porosity and structural flexibilities. Desolvated studies of the mixed-ligand MOFs revealed drastic void space reductions (to 3.7 and 5.7% for 1′ and 2′, respectively, at 298 K) compared to the as-synthesised structures (potential void spaces of 21.6 and 22.3% for 1 and 2, respectively, at 298 K). Despite inaccessible void spaces at 195 K, significant CO2 sorption at this temperature indicated structural transformations enabling adsorption. Water vapour sorption at 298 K induced similar transformations, as confirmed by single-crystal X-ray diffraction, showcasing the dynamic adaptability of these frameworks. For the single-ligand MOFs, void space ranged from 12 to 25% of the unit cell volume, with notable differences between interpenetrated and non-interpenetrated structures. Comparison with Cu-based counterparts from the literature highlighted that the Zn-based MOFs exhibited superior N2 and H2 adsorption due to higher crystallinity and stability upon desolvation. However, Cu-based MOFs displayed stronger CO2 adsorption interactions, with two-step adsorption isotherms and higher Qst values (up to 31.8 kJ mol-1), reflecting greater framework flexibility. Water vapor sorption studies emphasised the stronger interaction of Cu-based MOFs with unsaturated Cu(II) metal sites. These findings underscore the potential of Zn-based MOFs for gas storage and the dynamic structural responses of the mixed-ligand frameworks.